Integrasi Teknologi Jakarta Smart City dengan Sistem Komando dan Kendali untuk Penguatan Pertahanan Negara - Sarjito, Aris; Risdhianto, Agung (Contemporary Public Administration Review, 2025)
Jakarta Smart City, established under Governor Regulation No. 306 of 2016, holds significant potential to support the Command, Control, Communications, Computers, Intelligence, Surveillance, and Reconnaissance (C4ISR) system in strengthening national defense. By leveraging integrated technologies, Jakarta Smart City provides real-time data from many sectors such as transportation, logistics, and emergency management, which are highly relevant for strategic decision-making. This study aims to explore the potential, identify challenges, and formulate integration strategies between Jakarta Smart City technology and the C4ISR system. The research employs a qualitative approach with descriptive analysis based on secondary data from policy documents, official reports, and recent literature. Findings reveal that Jakarta Smart City can enhance intelligence, command, and control functions through real-time data and technological infrastructure, such as AI-powered CCTV and IoT sensors. However, significant challenges remain, including technological gaps between civilian and military systems, data security risks, and insufficient cross-agency coordination. In conclusion, successful integration requires improved interoperability between systems, enhanced cybersecurity measures, and updated national regulations to support synergy between civilian and military technologies. With these strategic measures, Jakarta Smart City can serve as a critical asset in bolstering national defense capabilities.